2019
DOI: 10.1183/13993003.01524-2018
|View full text |Cite
|
Sign up to set email alerts
|

Obesity alters oestrogen metabolism and contributes to pulmonary arterial hypertension

Abstract: Obesity is a common comorbidity for pulmonary arterial hypertension (PAH). Additionally, oestrogen and its metabolites are risk factors for the development of PAH. Visceral adipose tissue (VAT) is a major site of oestrogen production; however, the influence of obesity-induced changes in oestrogen synthesis and metabolism on the development of PAH is unclear. To address this we investigated the effects of inhibiting oestrogen synthesis and metabolism on the development of pulmonary hypertension in male and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…In this study, the group with a higher proportion of smokers has a higher incidence of prolonged MV. 2The adipose tissue creates a number of estrogens in overweight and obese patients that play an important role in pulmonary hypertension and remodeling [37] . It generally focuses on the changes in pulmonary and chest wall structures, which led to the increase of residual lung volume and chest wall impedance, a decrease of lung compliance and ventilation driving force, and abnormal ventilation-perfusion [38] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the group with a higher proportion of smokers has a higher incidence of prolonged MV. 2The adipose tissue creates a number of estrogens in overweight and obese patients that play an important role in pulmonary hypertension and remodeling [37] . It generally focuses on the changes in pulmonary and chest wall structures, which led to the increase of residual lung volume and chest wall impedance, a decrease of lung compliance and ventilation driving force, and abnormal ventilation-perfusion [38] .…”
Section: Discussionmentioning
confidence: 99%
“…However, we have shown that CYP1B1 is upregulated in white adipose tissue in obese mice and is involved in mediating the production and release of the mitogenic estrogen metabolite 16OHE1. 7 Obesity, estrogen metabolism and PAH Estrogen metabolism also plays a key role in PAH. As described above, there is an abundance of CYP1B1 in adipose tissue.…”
Section: Obesity and Cyp1b1mentioning
confidence: 99%
“…On the other hand, the proproliferative estrogen metabolite 16OHE1 induces pulmonary vascular remodelling and may promote insulin resistance in PAH. 7,9 For example, Fessel et al 9 found that treating BMPR2-mutant vascular smooth muscle cells with 16OHE1 significantly decreased mobilization of the glucose transporter Glut4 in response to insulin and expression of PPAR-g and lipid transporter CD36. Based on a proof-of-concept study, 16OHE2 has recently been hypothesized to be a mediator of PAH.…”
Section: Obesity and Cyp1b1mentioning
confidence: 99%
See 2 more Smart Citations